Assessing the efficacy of electrolyzed water for sanitizing contaminated stainless-steel surfaces in the meat industry - Khalid, Nurul Izzah; Sulaiman, Nurul Shaqirah; Ab Aziz, Norashikin; Taip, Farah Saleena; Mahmud Ab Rashid, Nor-Khaizura; Sobri, Shafreeza; Abd Rahim, Muhamad Hafiz (Elsevier, 2024)
Electrolyzed water (EW) presents promising potential as an alternative sanitation solution, offering cost savings and eliminating the need for harsh chemicals in food factories. This study investigates EW's efficacy in cleaning contaminated stainless-steel plates. Some plates were covered with meat residues, and the upper side of the plate's surfaces were inoculated with Escherichia coli ATCC 10536. Plates were then immersed in sterile distilled water (SDW) (pH: 7 ± 1), acidic electrolyzed water (AcEW) (free chlorine: 4.21 ± 0.05 mg/L, oxidation-reduction potential (ORP): 1168 ± 3.54 mV, pH: 2.74 ± 0.03), or alkaline electrolyzed water (AlEW) (ORP: 817 ± 8.49 mV, pH: 11.38 ± 0.01), at different temperatures (30 or 50 °C) for 30 s. The cleanliness of plates was confirmed microbiologically when no E. coli was detected, (below 1.0 log CFU/cm2). Treatment with SDW resulted in a modest reduction of the E. coli by 1.67 ± 0.84 log CFU/cm2 (±70% of the survived population). At 30 °C, E. coli was undetectable when AlEW was used without meat residue. At 50 °C, E. coli was undetectable when either AcEW or AlEW was used without meat residue. Visual and tactile inspections were conducted to validate cleanliness. The visual examination was performed after cleaning the plates with EW to ensure they appeared clean. However, tactile inspection indicated the presence of residues. Subsequent microbial analysis revealed 1.50 ± 0.87 log CFU/100 cm2 (±36% of the surviving population) of E. coli. This study demonstrated that meat residues on food-contact surfaces create a barrier to sanitation, necessitating mechanical action and heat for improved cleanliness.